Ionically crosslinked (meth) acrylic (co) polymers

By introducing pendant acid and ionic crosslinking agent into the (meth)acrylic acid copolymer, the gap between traditional thermosetting materials and thermoplastics in terms of processability and circulation is solved, and the processability and circulation of traditional thermosetting materials and thermoplastics is achieved. High mechanical and thermal stability and promotes reversibility and recyclability of the material.

CN119161685APending Publication Date: 2024-12-20TRINSEO EURO GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410791024.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-20
Filing Date
2024-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to prepare recyclable polymer crosslinking networks with desired mechanical and thermal stability through economically feasible ways, and there is a gap in processability and cyclability between conventional thermosetting materials and thermoplastics.

Method used

Using a reversible crosslinked (meth)acrylic acid copolymer composition, by adding 0.01% to 20% by weight of unsaturated acid or anhydride having pendant acid and/or anhydride groups to the (meth)acrylic acid copolymer chain Monomers, and 0.1% to 20% by weight of ionic crosslinking agent, form reversible crosslinking copolymers, crosslinking is achieved using ionic bonding or complexing reactions, and reverse crossover by temperature changes or addition of acid/aldehyde Coupon.

Benefits of technology

A balance of high melt strength and processability is achieved, reversible thermosetting properties are provided, cycleability and reprocessability are promoted, creep resistance, chemical resistance and scratch resistance are improved, suitable for composites Materials and a variety of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161685A_ABST
    Figure CN119161685A_ABST
Patent Text Reader

Abstract

Reversibly crosslinked (meth) acrylic copolymer compositions are disclosed. The composition comprises a) a (meth) acrylic copolymer chain comprising from 60% to 99.9% by weight of methyl methacrylate monomer units, and from 0.01% to 15% by weight of unsaturated acid or anhydride monomer units having draping acid and / or anhydride groups, and b) 0.1% to 20% by weight of one or more ionic cross-linking agents having at least one metal cationic group having a valence of 2 or more. The composition is capable of forming a reversible cross-link between pendant unsaturated acid or anhydride groups on other polymer chains by ionic bonding or complexation to form a cross-linked copolymer. Another composition includes one or more (meth) acrylic copolymer chains having from 0.1 wt% to 20 wt% of one or more unsaturated acid and / or anhydride groups pendant from the copolymer. A portion of the copolymer chains are reversibly crosslinked with other copolymer chains by i) ionic bonding or ii) complexation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ionically crosslinkable (meth)acrylic acid copolymers. The present invention also relates to ionically crosslinked (meth)acrylic acid copolymers, wherein the ionic crosslinks are reversible. Background Art

[0002] Thermoplastic polymers and copolymers, especially (meth)acrylic polymers, have excellent characteristics such as transparency, mechanical properties and processability. They are widely used in various fields such as automotive parts, electrical parts, industrial parts, optical materials, various parts of home appliances, aesthetic parts, sundries, etc.

[0003] In general, the melt strength of acrylic polymers increases with increasing molecular weight - providing improved mechanical properties in thermoplastics, such as creep resistance, scratch resistance and chemical resistance. However, as molecular weight increases, processability generally becomes more difficult. For demanding applications, the properties / processability balance is between thermosets and thermoplastics.

[0004] Reversible dynamic connections in polymer networks can bridge the gap between traditional thermosets and thermoplastics while promoting recyclability and reprocessability. However, the preparation of recyclable polymer crosslinked networks with desired mechanical and thermal stability via an economically viable route remains an industrial challenge. WO2020115023 describes ionomers of copolymers with vinylidene aromatic monomers and unsaturated compounds with acid groups. Summary of the invention

[0005] In one embodiment, a reversibly crosslinked (meth)acrylic copolymer composition is provided, comprising a) (meth)acrylic copolymer chains comprising 60 wt % to 99.9 wt % of methyl methacrylate monomer units, and 0.01 wt % to 15 wt % of unsaturated acid or anhydride monomer units having pendant acid and / or anhydride groups, and b) 0.1 wt % to 20 wt % of one or more ionic crosslinking agents having at least one metal cation group having a valence of 2 or greater.

[0006] The composition can form reversible crosslinks between pendant unsaturated acid or anhydride groups on other polymer chains by ionic bonding or complexation to form crosslinked copolymers.

[0007] In another embodiment, a composition is provided comprising one or more (meth)acrylic copolymer chains having from 0.1 wt % to 20 wt % of one or more unsaturated acid and / or anhydride groups pendant from the copolymer, and wherein a portion of the copolymer chains are cross-linked with other copolymer chains by i) ionic bonding or ii) complexation. The cross-links are reversible. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 :

[0009] Storage modulus of PMMA-ionomer as a function of temperature compared to non-crosslinked base polymer. Rubber plateau appears after crosslinking.

[0010] Figure 1 shows a graph of the storage modulus of a (meth)acrylic acid-ionomer as a function of temperature compared to a non-crosslinked base polymer;

[0011] Figure 2 Describes the controlled reversibility of (meth)acrylic acid ionomers generated in situ during polymerization; and

[0012] Figure 3 A graph showing the full cycle reversibility of (meth)acrylic acid-ionomers. DETAILED DESCRIPTION

[0013] As used herein, "copolymer" means a polymer having two or more different monomer units, including copolymers and polymers having three or more different monomers, such as terpolymers and tetrapolymers. Therefore, the term "copolymer, terpolymer and tetrapolymer" covers any polymer having more than one type of comonomer. "Polymer" is used to mean homopolymers and copolymers. The polymer may be linear, branched, star-shaped, comb-shaped, block or any other structure. The polymer may be homogeneous, heterogeneous, and may have a gradient distribution of comonomer units. All cited documents are incorporated herein by reference. As used herein, unless otherwise described, percentages shall mean weight percentages. Molecular weight is the weight average molecular weight measured by gel permeation chromatography (GPC) using polymethyl methacrylate standards. In the case where the polymer contains some crosslinking and GPC cannot be applied due to the insoluble polymer fraction, the weight average molecular weight is determined using the soluble fraction / gel fraction or soluble fraction molecular weight after extraction from the gel.

[0014] As used herein, "(meth)acrylic acid" or "(meth)acrylate" refers to both acrylate and methacrylate.

[0015] As used herein, so-called "crosslinked" refers to that multiple copolymers of the present invention are connected to other copolymers of the present invention by ionic bonds. Ionic bonds are formed by anions from unsaturated acids or anhydride groups on the copolymer chains and cations formed by ionic crosslinking groups, or by complexes of acid or anhydride groups and metal oxides. The metal oxide and the crosslinking group have a valence of at least 2. The valence of at least 2 means that the metal of the crosslinking group can form at least two cationic species. These cationic species can form bonds with anions, or can be complexed with at least two acid and / or anhydride groups. The copolymers of the present invention can form two or more crosslinks with other copolymers.

[0016] The reversibly crosslinked (meth)acrylic copolymer composition of the claim comprises a (meth)acrylic copolymer having pendant acid and / or anhydride groups and one or more ionic crosslinking groups. Once crosslinked, the (meth)acrylic acid-ionomer has both high melt strength and processability by changing the apparent molecular weight through reversible bonds.

[0017] (Meth)acrylic acid copolymer:

[0018] The (meth)acrylic acid copolymer contains 0.01 wt % to 20 wt %, preferably 0.1 wt % to 15 wt % of one or more unsaturated acid and / or anhydride monomer units, wherein the acid and / or anhydride groups are pendant from the copolymer. Examples of suitable acid or anhydride monomer units include, but are not limited to, acrylic acid, methacrylic acid, itaconic acid, maleic anhydride, vinyl benzoic acid, maleic acid, fumaric acid, 4-styrenesulfonic acid.

[0019] In a preferred embodiment of the present invention, the copolymer contains at least 50% by weight of methyl methacrylate monomer units, preferably at least 70% by weight and more preferably at least 80% by weight of methyl methacrylate monomer units in the copolymer.

[0020] In some embodiments, in addition to acid and / or anhydride monomers and methyl methacrylate, the copolymers of the present invention may include 0 wt % to 49.5 wt % of other acrylate and methacrylate monomers or other ethylenically unsaturated monomers, including but not limited to styrene, alpha methyl styrene, acrylonitrile, and low levels of crosslinking agents may also be present in the monomer mixture. Suitable acrylate and methacrylate comonomers include but are not limited to methyl acrylate, ethyl acrylate and ethyl methacrylate, butyl acrylate and butyl methacrylate, isooctyl methacrylate and isooctyl acrylate, lauryl acrylate and lauryl methacrylate, octadecyl acrylate and octadecyl methacrylate, isobornyl acrylate and isobornyl methacrylate, methoxyethyl acrylate and methoxymethylacrylate, 2-ethoxyethyl acrylate and 2-ethoxyethyl methacrylate, and dimethylaminoethyl acrylate and dimethylaminoethyl methacrylate monomers. In addition to acid and / or anhydride functional groups, other functional groups can be added to the (meth)acrylic copolymer through functional comonomers (including epoxy groups (such as glycidyl methacrylate) and hydroxyl groups). Functional monomer units comprising acid and anhydride functional monomer units may be present in up to 70% by weight of the (meth)acrylic polymer.

[0021] In one embodiment, the (meth)acrylic copolymer has a high Tg of greater than 115°C, more preferably greater than 120°C, greater than 125°C, greater than 130°C, greater than 135°C, and even greater than 140°C. Useful high Tg monomers include, but are not limited to, tert-butylcyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, α-methylstyrene, maleimide, isobornyl methacrylate, norbornyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, acrylamide, and methacrylamide. The high Tg monomer units may be present at a level of 0% to 25% by weight, more preferably 0% to 10% by weight.

[0022] Ionic crosslinking agent

[0023] Ionic crosslinking agents generally include one or more metal salts and / or one or more metal oxides having a metal valence of 2 or more. The metal can be any metal capable of forming two or more cationic groups, which will form ionic bonds with anions formed by acid and / or anhydride groups. The metal can be one or more of a transition metal, a post-transition metal, a metalloid and / or an alkaline earth metal. Preferred metals include zinc, zirconium, aluminum, magnesium, calcium and mixtures thereof. The metal is in the form of a salt or oxide, which can form cations under reaction conditions to form a crosslinked polymer. For example, the metal can exist in the form of a metal carbonate, a metal acetate, a metal bicarbonate, a metal oxide, a metal hydroxide, a metal carboxylate, a metal salt of a fatty acid or a mixture thereof.

[0024] Exemplary metal salts and / or metal oxides include, but are not limited to, zinc acetate, zinc acetylacetonate, zinc oxide, zinc oxalate, zinc carbonate, zinc hydroxide, zinc stearate, zinc citrate, zirconium acetate, zirconium oxide, aluminum acetate, calcium carbonate, and calcium stearate.

[0025] In one embodiment, the metal salt or metal oxide is part of a masterbatch, which may be a mixture of other components that may be used in the composition. The masterbatch may also include additives such as those listed below.

[0026] Additionally, the ionic crosslinking agent may be any basic substance that can be protonated by the pendant acid or anhydride groups to form an ion pair, which is capable of bonding two different polymer chains together.

[0027] The ionic crosslinking agent is present in the composition at 0.01 to 20 wt %, preferably 0.1 to 15 wt %.

[0028] additive

[0029] The compositions of the present invention can be blended with typical additives used in thermoplastics. Additives can be added to the composition prior to crosslinking. Useful additives include, but are not limited to, fillers, surface modification additives, nucleating agents, foaming agents, flow promoters, fibers, antioxidants, UV stabilizers, processing aids, fibers, lubricants, heat stabilizers, flame retardants, synergists, pigments and other colorants, and other compatible polymers.

[0030] If used, such additives are used in an effective amount to achieve the desired result. Based on the weight of the entire composition, the amount can be 0.001% by weight or more, 0.01% by weight or more, 0.1% by weight or more, 1.0% by weight or more, 2.0% by weight or more, 3.0% by weight or more, and up to 40% by weight or less, 30% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, 5% by weight or less.

[0031] In a preferred embodiment, the composition is impact-modified. Useful impact modifiers include block copolymers, graft copolymers and core / shell impact modifiers. The content of the impact modifier can be adjusted to meet the toughness requirements of the composition end-use. In one embodiment, for compositions with high optical clarity, the refractive index of the impact modifier matches the matrix polymer. In this respect, refractive index matching refers to that the refractive index difference between the impact modifier and the matrix copolymer is positive or negative 0.02 or less, preferably less than 0.01, and most preferably less than 0.05. Based on the weight of the entire copolymer composition, the impact modifier can exist in 0 wt % to 60 wt %, preferably 1 wt % to 55 wt %, more preferably 5 wt % to 25 wt %.

[0032] Additionally, low Tg linear polymers can be used as impact modifiers. Certain copolymers, such as butyl acrylate-(meth)acrylic acid copolymers can act as ionically crosslinked impact modifiers.

[0033] Other polymer additives may include polycarbonates, polyurethanes, polysulfones, polyamides, polyolefins, including copolymers and terpolymers based on these polymers, and including linear, branched, block and grafted polymer structures.Examples of matting agents include, but are not limited to, cross-linked polymer particles of various geometries.

[0034] Cross-linking

[0035] The (meth)acrylic acid copolymer having acid and / or anhydride groups remains separate from the ionic crosslinking agent.The crosslinked copolymer may be formed by contacting the components under the conditions described herein.

[0036] The equivalent ratio of the acid and / or anhydride groups on the (meth) acrylic copolymer to the ionic crosslinking agent can be selected so that when the components react, a crosslinked copolymer is formed. The equivalent ratio of the acid or anhydride groups to the ionic crosslinking agent can control the level of crosslinking that may occur. By equivalent, it is meant the number of pendant acid or anhydride groups that can be used to react with the metal. In order to form a crosslinked polymer, anions based on the acid or anhydride groups of the copolymer react with cations formed by metal salts and / or metal oxides having a valence of 2 or more. The degree of crosslinking is controlled by the lower amount of the acid or anhydride groups, or the amount of the metal salt or metal oxide. The amount of the acid or anhydride can be the limiting factor, or the amount of the metal salt or metal oxide can be the limiting factor. The equivalent ratio of the metal salt or metal oxide to the acid or anhydride groups can be about 1:40 or more, 1:20 or more, or 1:10 or more. The equivalent ratio of the acid or anhydride groups to the metal salt or metal oxide can be 1:40 or more, 1:20 or more, or 1:10 or more.

[0037] One of ordinary skill in the art will appreciate that a variety of methods can be used to contact the copolymer and the ionic crosslinking agent. Exemplary methods include during the polymerization process; by solution blending; and melt blending, such as by extrusion, injection molding, foam extrusion, and sheet extrusion.

[0038] In the solution process, the acid and / or anhydride functional (meth)acrylic copolymer is dissolved in an organic solvent and then mixed with an ionic crosslinker. The (meth)acrylic copolymer and the ionic crosslinker must be soluble in the organic solvent. The crosslinking reaction occurs rapidly. The solvent is then removed. This process can be used, for example, for pultrusion and fiber-reinforced composites.

[0039] In melt blending, the copolymer and ionic crosslinker are melt blended, preferably under vacuum, and extruded or injection molded. The extruded product can be formed into pellets, or thermoformed. The limitation of this method is that the crosslinking density is limited by the maximum torque of the processing equipment.

[0040] The temperature at which the components are contacted is 180° C. to 260° C., preferably 200° C. to 250° C., and more preferably 220° C. to 245° C. The contact time is long enough to allow the copolymer chains to be crosslinked by the ionic crosslinking groups. Preferably the contact time is 0.1 to 10 minutes, preferably 0.3 to 5.0 minutes, and more preferably 0.5 to 3.0 minutes.

[0041] Acids or aldehydes are generated during the cross-linking process and can be removed to drive the reaction to completion.

[0042] Crosslinking during the polymerization process involves polymerizing the monomers in the presence of an ionic crosslinking agent. The monomers and ionic crosslinking agent must be miscible. The advantage of this method is that it is a single unit operation. The method can be used to form composite materials, for vacuum infusion and for forming cast sheets.

[0043] In an exemplary embodiment, the crosslinking reaction occurs between 80 wt % to 99.9 wt % of the free acid-containing (meth)acrylic acid copolymer and 0.1 wt % to 20 wt % of zinc acetate as shown below:

[0044]

[0045] A (meth)acrylic acid copolymer containing free acid groups (e.g., (meth)acrylic acid) and a multivalent metal salt (e.g., zinc acetate) can be melt blended by extrusion. The acetate ions are exchanged, and the zinc ions crosslink the (meth)acrylic polymer chains. The acetic acid is then removed by vacuum. Adding excess acetic acid reverses the crosslinked polymer back to the initial uncrosslinked state.

[0046] The crosslinks are reversible. The reversibility of the crosslinks facilitates processing of the copolymer composition. Reversibility can occur by subjecting the crosslinked copolymer to a temperature at which the ionic bonds break under shear and / or contacting the composition with an excess equivalent of an acid or aldehyde such that the crosslinks are reversed. Typically, the temperature for breaking the crosslinks is 180°C to 260°C, preferably 190°C to 255°C, and more preferably 200°C to 250°C. The crosslinks can also be broken or reversed by adding an acid or aldehyde. Exemplary acids include, but are not limited to, acetic acid, an aldehyde of the formula CH3(CH2) n The crosslinking is preferably carried out in an amount of 1:1 to 10,000:1, preferably 5:1 to 5,000:1, and more preferably 10:1 to 4,000:1. The crosslinking is reversed until the solution viscosity of the copolymer after the crosslinking is reversed is substantially the same as before the crosslinking. By substantially the same, it is meant that the solution viscosity after the crosslinking is reversed is 5% of the original solution viscosity before the crosslinking.

[0047] characteristic

[0048] The compositions disclosed herein can provide high molecular weight resins with processability. Advantages of the compositions include one or more of the following:

[0049] - Improves creep, chemical and scratch resistance.

[0050] - Potential for producing ultra-tough (meth)acrylic thermoplastics.

[0051] - Reversible thermosetting properties. This provides sustainability and recyclability.

[0052] - Improves melt strength, thus providing better thermoforming properties.

[0053] application

[0054] The claimed composition can be used in any application where thermoplastics and thermosets are used by combining the properties of both for a fully reversible crosslinking system.

[0055] One useful application is in products that require strong material properties, but are recyclable. Crosslinking provides the properties of very high molecular weight polymers, but can be recycled by reversing the crosslinking. In composites, fibers and non-plastic materials can be recycled.

[0056] Another useful application is in materials requiring high creep resistance, and where thermoset-like properties are desired. This includes composites using glass fibers, carbon fibers, natural fibers, or combinations thereof. The fiber materials may be oriented, unidirectional, or woven into one or more layers.

[0057] In addition to composites, the claimed compositions can be used in cast or extruded sheets, thermoformed articles, injection molded articles (to reduce cycle time), toys, automotive parts, RVs, solar panels, windmills, building parts, medical devices, electronic devices, printed circuit boards, implants, robots, household appliances, kitchen appliances, display devices, etc.

[0058] Example

[0059] Melt Flow Rate (MFR) Measurement The melt flow rate of the polymer was measured using an Instron Ceast MF30 device. The mold temperature was controlled at 230°C and the load cell weight was 3.8 kg. The dried pellets were heated below T g Use within 8 hours at a temperature close to 20°C.

[0060] Gel Permeation Chromatography (GPC) : Polymer molecular weight measurements (Mw, Mn, Mz) were performed using a Waters Alliance 2695 and a Waters differential refractometer 2410. The columns were based on two PL Gel mixed C columns and a guard column (7.8 mm ID×30 cm, 5 μm). THF (HPLC grade) was chosen as the solvent. The temperature was controlled at 35°C. Ten poly(methyl methacrylate) standards were used in the calibration, with M p (peak molecular weight) ranges from 550 g / mole to 1,677,000 g / mole.

[0061] Weight average molecular weight (Mw), number average molecular weight (Mn) and Z average molecular weight (Mz) Differential Scanning Calorimetry (DSC) : During the second heating, the glass transition temperature of the (meth)acrylic polymer was measured using a TA Instruments Q2000 DSC at a heating rate of 10°C / min in N2. The first heating was used to heat the sample to 170°C at a heating rate of 10°C / min, and then the sample was cooled to 0°C at a cooling rate of 10°C / min. The sample weight was controlled at 5-10 mg.

[0062] Tensile strength and elongation : After 23°C / 48 hours preconditioning, tensile strength, modulus and elongation of tensile bars were evaluated using ASTM D638 method using Instron Model 4202 at a crosshead speed of 5 mm / min. The tensile length was 6" and the width was 0.50". The sample thickness was 0.125".

[0063] Vicat softening temperature: Samples were tested in an Instron HV6M using ASTM method D1525 at 10 N and 50 N forces. Sample heating rate was controlled at a rate of 50 °C / hour. Injection molded samples were annealed at about 20 °C below Tg for 16 hours and stored in a drying oven before testing.

[0064] Unless otherwise stated, solution viscosity Measured with a Brookfield-Spindle 3 at 100 rpm.

[0065] Torque : Read the torque value from the measuring instrument on the human machine interface (PMI) (also known as the user interface). This is a percentage value of the maximum torque. Power [kW] = Torque [Nm] * RPM [RPM] / 9550. At a constant RPM, the torque % is directly related to the power consumption. Increasing the melt viscosity means increasing the power to keep up with the RPM. Although ionic crosslinking is reversible, it will increase the melt viscosity of the polymer. Therefore, the torque limit or power limit of the extruder can limit the increase of ionic crosslinking density beyond a threshold.

[0066] Storage modulus : Torsional dynamic mechanical measurements were performed according to ASTM D5279-13.

[0067] Sample size 10×4×25 mm. Temperature scan -150°C to 170°C. Oscillation frequency 10 rad / s, applied strain 0.1%. Normal force = -1 N

[0068] HDT : Flat HDT according to ISO 75-1 and ISO 75-2. Load 1.80 MPa (method A), heating rate 120°C / h. Sample dimensions 10×4×80 mm. Support distance 64 mm. The test ends at a strain of 0.2%.

[0069] Dynamic Melt Rheology (Melt viscosity)

[0070] Parallel plate method according to ASTM D4440-07. Plate diameter 25 mm, measuring gap 1.000 mm. Frequency sweep logarithm from 628.13 rad / s to 0.314 rad / s at the desired temperature. Applied strain 1%.

[0071] Material

[0072] The materials listed in Table 1 are commercially available copolymers of methyl methacrylate with methacrylic acid (MAA) and ethyl acrylate (EA) from Trinseo ( Resin). Zinc acetate dihydrate Zn(OAc)2 was used as is. V825T was used as a non-functional reference poly(methyl methacrylate) (pMMA).

[0073] Table 1. Names, chemical compositions and characteristics of PMMA grades

[0074]

[0075]

[0076] Example 1: Ionic crosslinking in solution

[0077] 15g polymer sample is dissolved in 150g dichloromethane (DCM), zinc acetate (ZnAc) or zinc acetylacetonate (ZnAcAc) is added, and the mixture is shaken (IKA shaker) in a bottle at room temperature for 72 hours. All samples containing methacrylic acid (MAA) show that the solution viscosity increases. PMMA-3 and PMMA-4 show the most significant changes after adding Zn-salt, and their viscosity reverses after adding excessive acetic acid. This proves that reversible ionic crosslinking has been formed to form PMMA-ionomer. The results are summarized in Table 2.

[0078] Table 2. Preparation of pMMA-ionomers in DCM, demonstrating reversibility of ionic crosslinking as evidenced by changes in solution viscosity.

[0079]

[0080] Example 2. Production of PMMA-ionomer by extrusion

[0081] 50 g polymer samples were extruded in a ThermoFisher Haake Minilab twin screw extruder with zinc acetate at 200 rpm and 250 °C. The torque was recorded after the addition of zinc acetate. PMMA-4, which has the highest MAA level, showed a significant increase in torque during extrusion, indicating the formation of strong bonds and an increase in polymer molecular weight. The results are summarized in Table 3. Figure 1 As shown, ionically crosslinked polymers exhibit significantly increased melt strength while maintaining processability.

[0082] Table 3. Preparation of PMMA-ionomers using Haake Minilab twin-screw extruder

[0083]

[0084] Example 3. In-situ production of PMMA-ionomers during polymerization:

[0085] Methyl methacrylate (MMA) was polymerized in the presence of methacrylic acid (MAA) and Zn salts to test in situ ionomer formation during polymerization. The monomer ratios were used as shown in the table below. In each case, the MAA / Zn ratio was kept constant at 2 / 1. The polymerization was carried out in sealed vials without stirring. No chemical initiator or chain transfer agent was used. The total feed content was 25 g / vial. The results are shown in Figure 2 middle.

[0086] Table 4. Composition of MMA-MAA-Zn PMMA ionomers

[0087]

[0088]

[0089] Table 5. Changes in solubility and molecular weight after polymerization and decrosslinking by acetic acid. Molecular weight distribution by GPC The area under the curve measures solubility

[0090]

[0091] Example 4. Full cycle reversibility test of PMMA ionomer:

[0092] PMMA-3 and PMMA-4 were crosslinked by ZnAcAc in DCM. Acid / Zn was used in a 2 / 1 ratio. After crosslinking was complete, the gel network was decrosslinked using excess AcAc. The volatiles from this material, which contained all crosslinked and decrosslinked components, were removed in a vacuum oven. From the shear rate dependence of the melt viscosity measurements, it can be seen that the decrosslinked material returned to its original viscosity similar to The original state of PMMA-3 and PMMA-4. The data proves that these materials can be recycled through multiple cross-linking / de-cross-linking. Figure 3 .

[0093] While the present disclosure has been described in conjunction with specific embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the scope of the claims, the scope of which is to be given the broadest interpretation to encompass such modifications and equivalent structures.

[0094] In one embodiment, a reversibly crosslinked (meth)acrylic copolymer composition comprises: a) (meth)acrylic copolymer chains comprising 60 wt % to 99.9 wt %, preferably 75 wt % to 99 wt % and most preferably 80 wt % to 95 wt % of methyl methacrylate monomer units, and 0.01 wt % to 20 wt %, preferably 0.1 wt % to 15 wt % of unsaturated acid or anhydride monomer units having pendant acid and / or anhydride groups, and optionally 0.1 wt % to 25 wt % of % to 15 wt % of one or more ionic crosslinking agents, wherein the crosslinking agent comprises at least one metal cation group, wherein the metal cation group has a valence of 2 or more; wherein at least a portion of the (meth)acrylic copolymer is capable of forming crosslinks with the pendant unsaturated acid or anhydride monomer units on other polymer chains by ionic bonding or complexing with the ionic crosslinking agent to form a crosslinked copolymer.

[0095] The reversibly crosslinked (meth)acrylic copolymer composition in the above-described embodiment, wherein the crosslinks between the acrylic copolymer chains are reversible, and wherein the weight average molecular weight of the copolymer chains before crosslinking and after breaking the crosslinks are substantially the same.

[0096] The reversibly crosslinked (meth)acrylic copolymer composition of the embodiment described above, wherein the melt viscosity of the (meth)acrylic copolymer chain after crosslinking is at least 10% higher than the melt viscosity of the (meth)acrylic copolymer chain before crosslinking when measured at 200°C and 0.314s angular frequency.

[0097] In the reversibly crosslinked (meth)acrylic copolymer composition of the above-described embodiment, the metal cation group is a metal salt of one or more salts selected from transition metals, metalloids and alkaline earth metals, and the transition metals, metalloids and alkaline earth metals are preferably selected from zinc, zirconium, aluminum, magnesium and calcium.

[0098] The reversibly crosslinked (meth)acrylic copolymer composition of the above-described embodiment, wherein the solution viscosity of the crosslinked (meth)acrylic copolymer measured at 10 wt % in dichloromethane at 23° C. is at least 100% greater than the solution viscosity of the uncrosslinked (meth)acrylic copolymer.

[0099] The reversibly crosslinked (meth)acrylic copolymer composition of the above-described embodiment, wherein the equivalent ratio of the metal ions on the copolymer to the equivalents of anions formed by the pendant acid or anhydride groups is 40:1 to 1:40.

[0100] The reversibly crosslinked (meth)acrylic copolymer composition in the above embodiment further comprises 1 to 60 wt % of an impact modifier, preferably 5 to 25 wt % of an impact modifier, based on the weight of the entire copolymer composition.

[0101] The reversibly crosslinked (meth)acrylic copolymer composition in the above-described embodiment, wherein the ionic crosslinking agent is selected from the group consisting of metal carbonates, metal acetates, metal bicarbonates, metal oxides, metal hydroxides, metal carboxylates, metal acetylacetonates, metal salts of fatty acids, zinc acetate, zinc oxide, zinc carbonate, zinc hydroxide, zinc stearate, zinc citrate, zirconium acetate, zirconium oxide, aluminum acetate, calcium carbonate and calcium stearate, and mixtures thereof.

[0102] In one embodiment, a method for preparing a reversibly crosslinked (meth)acrylic acid from a reversibly crosslinked (meth)acrylic acid copolymer composition of the above-described embodiment comprises contacting the (meth)acrylic acid copolymer having unsaturated acid or anhydride monomer units with pendant acid or anhydride groups with one or more ionic crosslinking agents under conditions such that a portion of the pendant acid or anhydride groups are crosslinked with other (meth)acrylic acid copolymer chains.

[0103] In the method of the above-described embodiment, the (meth)acrylic acid copolymer is dissolved in an organic solvent and mixed with the ionic crosslinking agent.

[0104] The method in the above-described embodiment, wherein the (meth)acrylic acid copolymer and the ionic crosslinking agent are melt-blended under vacuum.

[0105] In the method of the above-described embodiment, the methyl methacrylate, the unsaturated acid and / or anhydride monomer and optionally other monomers capable of polymerizing with methyl methacrylate and the unsaturated acid and / or anhydride are polymerized in the presence of the ionic crosslinking agent.

[0106] The reversibly crosslinked (meth)acrylic copolymer composition in the above-described embodiment, wherein the composition is part of a composite material, a cast or extruded sheet, a thermoformed article, an injection molded article, a toy, an automotive part, a recreational vehicle, a solar panel, a windmill, a building component, a medical device, an electronic device, a printed circuit board, an implant, a robot, a household appliance, a kitchen appliance, or a display device.

[0107] In one embodiment, a composition comprising one or more (meth)acrylic copolymer chains having from 0.1 wt% to 20 wt%, more preferably from 0.1 wt% to 15 wt% of one or more unsaturated acids and / or anhydrides, wherein the acids and / or anhydrides are pendant from the copolymer; wherein a portion of the copolymer chains are crosslinked with other copolymer chains by i) ionic bonding of anions formed by the pendant acid or anhydride groups with metal cations having a valence of 2 or greater, or ii) complexation between the pendant acid or anhydride groups and metal oxides.

[0108] The composition of the above-described embodiment, wherein the crosslinking is reversible, and the weight average molecular weight of the copolymer after the crosslinking is reversed is substantially the same as it was before the crosslinking.

Claims

1. A reversibly crosslinked (meth)acrylic acid copolymer composition comprising: a) (meth)acrylic copolymer chains comprising 60 to 99.9 wt %, preferably 75 to 99 wt % and most preferably 80 to 95 wt % of methyl methacrylate monomer units, and 0.01 to 20 wt %, preferably 0.1 to 15 wt % of unsaturated acid or anhydride monomer units having pendant acid and / or anhydride groups, and optionally 0.1 to 25 wt % of other monomers capable of polymerizing with the methyl methacrylate and unsaturated acid or anhydride monomers; b) 0.01 wt% to 20 wt%, more preferably 0.1 wt% to 15 wt% of one or more ionic crosslinking agents, wherein the crosslinking agent comprises at least one metal cation group, wherein the metal cation group has a valence of 2 or greater; wherein at least a portion of the (meth)acrylic acid copolymer is capable of forming crosslinks with pendant unsaturated acid or anhydride monomer units on other polymer chains by ionic bonding or complexing with the ionic crosslinking agent to form a crosslinked copolymer, The copolymer composition is characterized in that: The composition further comprises from 1 to 60 wt % of at least one impact modifier, preferably from 5 to 25 wt % of at least one impact modifier, based on the weight of the entire copolymer composition, The at least one impact modifier is a butyl acrylate-(meth)acrylic acid copolymer.

2. The reversibly cross-linked (meth)acrylic copolymer composition of claim 1, wherein the cross-links between the acrylic copolymer chains are reversible, and wherein the weight average molecular weight of the copolymer chains before cross-linking and after breaking the cross-links are substantially the same.

3. The reversibly crosslinked (meth)acrylic copolymer composition of claim 1, wherein the melt viscosity of the (meth)acrylic copolymer chains after crosslinking is at least 10% higher than the melt viscosity of the (meth)acrylic copolymer chains before crosslinking when measured at 200°C with an angular frequency of 0.314 s.

4. The reversibly crosslinked (meth)acrylic copolymer composition of claim 1, wherein the metal cation group is a metal salt selected from one or more salts of transition metals, metalloids and alkaline earth metals, preferably selected from zinc, zirconium, aluminum, magnesium and calcium.

5. The reversibly crosslinked (meth)acrylic copolymer composition of claim 1, wherein the solution viscosity of the crosslinked (meth)acrylic copolymer measured at 10 wt% in dichloromethane at 23°C is at least 100% greater than the solution viscosity of the uncrosslinked (meth)acrylic copolymer.

6. The reversibly crosslinked (meth)acrylic copolymer composition of claim 1, wherein the equivalent ratio of metal ions on the copolymer to equivalents of anions formed by pendant acid or anhydride groups is from 40:1 to 1:

40.

7. The reversibly crosslinked (meth)acrylic copolymer composition of claim 1, wherein the ionic crosslinking agent is selected from the group consisting of metal carbonates, metal acetates, metal bicarbonates, metal oxides, metal hydroxides, metal carboxylates, metal acetylacetonates, metal salts of fatty acids, zinc acetate, zinc oxide, zinc carbonate, zinc hydroxide, zinc stearate, zinc citrate, zirconium acetate, zirconium oxide, aluminum acetate, calcium carbonate and calcium stearate, and mixtures thereof.

8. A method for preparing a reversibly crosslinked (meth)acrylic acid from the reversibly crosslinked (meth)acrylic acid copolymer composition of claims 1 to 7, comprising contacting the (meth)acrylic acid copolymer having unsaturated acid or anhydride monomer units with pendant acid or anhydride groups with one or more ionic crosslinking agents under conditions such that a portion of the pendant acid or anhydride groups crosslink with other (meth)acrylic acid copolymer chains.

9. The method of claim 8, wherein the (meth)acrylic acid copolymer is dissolved in an organic solvent and mixed with the ionic crosslinking agent.

10. The method of claim 8, wherein the (meth)acrylic acid copolymer and the ionic crosslinking agent are melt blended under vacuum.

11. The method of claim 8, wherein the methyl methacrylate, unsaturated acid and / or anhydride monomers and optionally other monomers polymerizable with methyl methacrylate and the unsaturated acid and / or anhydride are polymerized in the presence of the ionic crosslinking agent.

12. The reversibly crosslinkable (meth)acrylic copolymer composition of claim 1, wherein the composition is part of a composite material, a cast or extruded sheet, a thermoformed article, an injection molded article, a toy, an automotive part, a recreational vehicle, a solar panel, a windmill, a building component, a medical device, an electronic device, a printed circuit board, an implant, a robot, a household appliance, a kitchen appliance, or a display device.

13. A composition comprising one or more (meth)acrylic copolymer chains having from 0.1 wt% to 20 wt%, more preferably from 0.1 wt% to 15 wt% of one or more unsaturated acids and / or anhydrides, wherein the acids and / or anhydrides are pendant from the copolymer; wherein a portion of the copolymer chains are cross-linked with other copolymer chains by: i) ionic bonding of anions formed by the pendant acid or anhydride groups with metal cations having a valence of 2 or more, or ii) complexation between the pendant acid or anhydride groups and metal oxides, The composition is characterized in that: The composition further comprises 1 to 60 wt % of at least one impact modifier, preferably 5 to 25 wt % of at least one impact modifier, The at least one impact modifier is a butyl acrylate-(meth)acrylic acid copolymer.

14. The composition of claim 13, wherein the crosslinks are reversible and the weight average molecular weight of the copolymer after the crosslinks are reversed is substantially the same as it was before the crosslinks.